Woman: An intimate geography - Angier, Natalie (Anchor Books, 2000)
Woman is a fascinating, fact-filled guide that covers everything from organs to orgasms, hormones to hysterectomies. With her characteristic clarity, insight, and sheer exuberance of language, bestselling author Natalie Angier cuts through the still-prevalent myths and misinformation surrounding the female body, that most enigmatic of evolutionary masterpieces. With a witty and assured narrative, and a reader-friendly dose of science, Woman is an essential and engaging resource for all time.
Keywords: amériques; approches et analyses; biologie; corps; cours; différence des sexes; discipline; fem1000; médecine; premier cycle; psychologie; rapports sociaux de sexe; régions géographiques; santé; sciences; sciences humaines; stéréotypes; thématiques; états-unis

Manifesta young women, feminism, and the future - Baumgardner, Jennifer (1970- ).; Richards, Amy (Farrar, Straus and Giroux, 2000)
In the year 2000, girl culture was clearly ascendant. From Lilith Fair to Buffy the Vampire Slayer to the WNBA, it seemed that female pride was the order of the day. Yet feminism was also at a crossroads; "girl power" feminists were obsessed with personal empowerment at the expense of politics, while political institutions such as Ms. and NOW had lost their ability to speak to a new generation. In Manifesta, Jennifer Baumgardner and Amy Richards brilliantly revealed the snags in each feminist hub, all the while proving that these snags had not imperiled the future of the feminist cause. The book went on to inspire a new generation of female readers, and has become a classic of contemporary feminist literature.
Keywords: 1900-1999; 1990-1999; amériques; cours; cycles supérieurs; fem1000; fem9000; militance; mouvements féministes; premier cycle; périodes historiques; régions géographiques; thématiques; états-unis; études culturelles

Debora et Judith : l’amour entre femmes dans l’église catholique. Et CIEL parlait, ce serait l’ENFER? - Bazinet, Colette (Recherches féministes, 2000)
Keywords: amériques; approches et analyses; compte-rendu; cours; discipline; fem1000; invisibilités; lesbianisme; premier cycle; québec; ressource en ligne; régions géographiques; science des religions; sciences humaines; sexualité; thématiques; église

Chronologie d’une émancipation. Questions féministes sur la citoyenneté des femmes - Cohen, Yolande (2000)
L’histoire des Québécoises et de leurs rapports complexes à la politique est étudiée dans ce texte à partir du prisme offert par l’analyse du phénomène des Yvettes, issu du référendum sur la souveraineté-association de 1980. Cet événement fournit l’occasion de repenser les liens qui se sont noués depuis le début du siècle entre féminin, féminisme et nationalisme. L’auteure propose une brève chronologie des principales stratégies féministes des Québécoises, qui permet de mieux appréhender les transformations politiques en cours. Elle y intègre les revendications dites sociales, qui sont souvent la raison d’être officielle des grandes organisations de femmes, comme la Fédération nationale Saint-Jean-Baptiste, les Cercles de Fermières, les AFÉAS, etc. En considérant les stratégies déployées par ces organisations pour combattre l’exclusion politique des femmes (qualifiées parfois de stratégies d’émancipation), elle identifie trois grands moments, qui sont aussi des moments clés de l’histoire politique du Québec contemporain. Au-delà de cette chronologie, qui permet de situer les lecteurs dans le contexte historique, la question de la construction politique d’une identité de genre au cours du XXe siècle est au centre de ce récit. Elle permet de comprendre comment s’est articulée la double revendication de la différence des sexes (ou la complémentarité des rôles sexués) et de l’égalité des droits, durant cette période.
Publisher: Globe, Revue internationale d’études québécoises Érudit
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; canada; cours; discipline; féminisme québécois; histoire; histoire et politique; justice sociale; militance; pol4102; premier cycle; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; sciences humaines; thématiques

Le siècle dans la tourmente du féminisme - Daigle, Johanne (Globe : revue internationale d’études québécoises, 2000)
L’empreinte du féminisme sur le XXe siècle québécois est indélébile. De l’aube au crépuscule du siècle, la « question des femmes » a coloré les grands débats, imprégné les luttes socio-politiques et laissé sa marque sur les systèmes de lois, les institutions, l’organisation du travail et les modes de vie. Cet article veut montrer comment, dans une perspective historique, la « question des femmes » — ainsi posée par les élites masculines — fut pressentie comme l’une des grandes interrogations de ce siècle et comment les changements survenus dans la reconfiguration des rapports entre hommes et femmes — des identités sexuelles aux modèles qui les supportent — restent au coeur des enjeux d’une société.
https://www.erudit.org/en/journals/globe/2000-v3-n2-globe1497493/1000582ar/
Keywords: 1900-1999; EDI; amériques; approches et analyses; conflit; cours; discipline; discours dominant; droits des femmes*; fem1000; histoire; histoire et politique; inégalités; militance; patriarcat; premier cycle; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; travail; épistémologie

Mort ou fif: la face cachée du suicide chez les garçons - Dorais, Michel; Lajeunesse, Simon Louis (VLB éditeur, 2000)
A partir de témoignages et récits de vie, cet ouvrage met en lumière la relation entre le mépris et l'ostracisme dont sont victimes les adolescents homosexuels ou considérés comme tels et leur haut taux de suicide. Une version revue et corrigée d'un document publié par le Centre de recherche sur les services communautaires de l'Université Laval (octobre 2000).
Section: 110 pages ; 23 cm
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; corps; cours; discipline; hétérosexisme; identités LGBTQIA2+; premier cycle; périodes historiques; queer; québec; régions géographiques; santé; shm4000; systèmes d'oppressions; thématiques

Genders - Glover, David; Kaplan, Cora (Routledge, 2000)
"Gender" has, in recent years, become one of the busiest terms in literary and cultural theory, as well as being one of the most contested. David Glover and Cora Kaplan chart the main lines of contemporary debate surrounding gender in a guide which:* presents a history of the term, from the sexology of psychoanalysis of the 1960s to its current usage within the interdisciplinary field of gender studies* looks at the major perspectives on gender from second-wave feminist writers and critics* examines new work on masculinity in literary and cultural studies* assesses how the creation of new queer and gendered identities has impacted the study of literature* surveys empirical and theoretical work on readership and spectatorship, looking in detail at modes of fantasy, cultural consumption, reader response and fan cultures.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; amériques; antiféminisme; approches et analyses; cours; culture populaire; discipline; fem1000; littérature; masculinisme; premier cycle; périodes historiques; queer; ressource en ligne; régions géographiques; états-unis; études culturelles; études littéraires

Something to tell you: the road families travel when a child is gay - Herdt, Gilbert H.; Koff, Bruce (Columbia University Press, 2000)
Even now, at the end of the twentieth century, many still have difficulty standing up and saying, "I am the parent of a gay child." Something to Tell You recounts the stories of families whose lives have been touched by the discovery that a child is lesbian or gay—how it affects and influences people's perceptions of their children and even changes the self-image of parents themselves. Focusing on fifty average families—not people seen in clinics or therapy—the authors found a consistent pattern of change: first negative, then positive. Sometimes the news led parents and siblings to form stronger bonds with the child, with each other, and with other relatives and friends. In many cases, their child's partner and partner's family grew to assume an important role in their own lives. In some cases, parents and siblings discovered new meaning in their lives through speaking out or joining PFLAG (Parents, Families, and Friends of Lesbians and Gays) and becoming part of the struggle for lesbian and gay rights. The authors found that families committed to staying together are typically able to overcome the powerful obstacles imposed by society. Something to Tell You also shows the lasting and sometimes tragic consequences for families who falter in the process of integration. Unwilling to accept their child's sexuality, some parents sought to blame each other, and all too often their own relationships unraveled as a result. Others who failed to tell close friends sometimes lost those friends through keeping secrets. Parents who neglected to form bonds with their child's partner fostered climates of alienation that persisted for years. A richly diverse collection of family stories, Something to Tell You is a book that will help break down widespread prejudice and put an end to destructive cultural myths. It affirms families' highest aspirations toward active love for their gay children, showing the steps to take toward new levels of support, solidarity, and love.
Section: xxii, 156 p. ; 24 cm.
Keywords: LGBTQIA2+; amériques; approches et analyses; cours; discipline; famille; hétérosexisme; patriarcat; premier cycle; relations familiales; régions géographiques; sciences humaines; soc2014; sociologie; systèmes d'oppressions; thématiques; états-unis

Expériences des femmes et théologie. La théologie « mujerista » : une nouvelle pratique théologique - Melançon, Louise (Laval théologique et philosophique, 2000)
Les théologies féministes sont plurielles de par la diversité des expériences qui leur donnent naissance. S'il est vrai que l'expérience du sexisme et de l'androcentrisme traverse les discours féministes, elle n 'en est pas moins contextuelle. La prise en compte de ces expériences des femmes en théologie interroge et commence à modifier la pratique même de la théologie. La théologie mujerista née de la survie des femmes hispano-américaines en est un exemple remarquable.
Keywords: amérique latine; amériques; approches et analyses; cours; discipline; fem1000; femmes*; intersectionnalité; inégalités; premier cycle; ressource en ligne; régions géographiques; science des religions; sciences humaines; sexisme; systèmes d'oppressions; théologie; états-unis